FENOMENA SISWA PEROKOK (STUDI KASUS DI SMA NEGERI 3 DEMAK) (Solidarity: Journal of Education, Society and Culture, 2013)
The background of students SMA 3 Demak a smoker? 2) How does the socialization process SMA 3 Demak students can become a smoker? 3) What is the response from the school and outside the school to see the phenomenon of students smoke?The study used a qualitative approach. Subjects consisted of five high school students Demak State 3, and three informants of the study. In collecting data, researchers used a technique of observation, focus group discussions, interviews, and documentation. And to check the validity of the data using triangulation techniques. The results of this study indicate that the background is the curiosity of students smoking, stress, weather, shame, wants to build a certain image, berekonomi capable. In conjunction with the socialization process of students becoming a smoker is not comfortable when you first smoked, ridiculed by others, were treated to smoking by others, the imitation of the behavior of others, feel comfortable to smoke